Predictive Validity of the HCR-20V3 With Incarcerated Males in Mexico City - Nijdam-Jones, Alicia (Criminal justice and behavior, 2021)
This prospective study investigated the predictive validity of the Historical-Clinical-Risk Management–20, Version 3 (HCR-20V3) in a sample of incarcerated males in a Mexico City prison. Data were collected from 114 male adults incarcerated in a medium-security prison in Mexico City. Participants were an average of 36.86 years old (SD = 9.93 years) and were all born in Mexico. Data collection for HCR-20V3 ratings involved clinical interviews and a review of institutional documents. Aggressive incidents for a 3-month period following each completed risk assessment were collected through document review, self-report follow-up interviews, and guard reports. Participants who engaged in institutional violence during the 3-month follow-up period were given significantly higher summary risk ratings and had higher HCR-20 total scores than the participants who did not engage in violence (area under the curve [AUC] ranged from .71 to .77). The study demonstrated support for the cross-cultural utility of the HCR-20V3 for institutional violence in a Mexican prison.